Broadband Millimeter-Wave Circularly Polarized Open-Ended Waveguide Antenna Using Stubs and Its Application in Forming an Array - Zhang, Jing-Yi; Zhang, Jin-Dong; Chen, Qiao-Yu; Wu, Wen; Fang, Da-Gang (IEEE transactions on antennas and propagation, 2023)
A new broadband circularly polarized (CP) antenna using an open-ended waveguide is proposed in this article. By using two stubs at different positions of the open-ended waveguide, the amplitude and phase of the orthogonal fields are effectively adjusted. The method is applied to the millimeter-wave bands, and a single element as well as a four-element array are presented. Reasonable agreement between the measured and simulated results has been observed. The antenna element has a wide overlapping impedance bandwidth of 50% and a 3 dB axial ratio (AR) bandwidth of 50% covering 24-40 GHz, making it a promising candidate for wideband applications. The measured realized gains at 28 and 38 GHz are 6.7 and 6.9 dBic for an element and 12.3 and 13.9 dBic for an array, respectively.